The Brill dictionary of Gregory of Nyssa - Mateo-Seco, Lucas F.; Maspero, Giulio (Leiden ; Boston : Brill, 2010)
"The Brill Dictionary of Gregory of Nyssa" is the fruit of wide-ranging collaboration between more than forty scholars from various disciplines and perspectives, providing in two hundred articles a symphonic vision of the studies on Gregory of Nyssa and his thought.
Preface; List of Contributors; List of Entries; Gegory'sWorks; List of Abbreviations; Dictionary of Gregory of Nyssa; Index of Names; Index of Biblical Citations; Thematic Readings.
Includes bibliographical references and indexes.
Print version record.
Master record variable field(s) change: 600
Keywords: Gregory, -- of Nyssa, Saint, -- approximately 335-approximately 394 -- Dictionaries; Gregory, -- of Nyssa, Saint, -- approximately 335-approximately 394; Gregorius (Nyssenus); RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Electronic books; Dictionaries